Penerapan Buku Kontrol Terhadap Pembiasaan Beribadah Shalat Dan Pembentukan Karakter Siswa Dengan Pemberikan Reward Terhadap Kelas 1 SDIT Insan Rabbani Sungai Geringging - Opet Sarianti; Nurfarida Deliani; Juliana Batubara (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan bahasa dan Sastra, 2024)
This research was conducted with the aim of improving the quality of student prayer and improving student character for the better, as well as good habits that must be formed considering that they have reached elementary school age which is an educational foundation that must be built firmly. The method in this research is field research with a qualitative descriptive approach. The results of this study are according to statements given by homeroom teachers, student guardians and students involved, indicating that the existence of prayer control books and giving rewards has a positive impact on students. Students better understand their obligations and are more motivated to pray and become accustomed to praying and help build the character of students who are honest and more obedient to parents' orders.